Prognostic relevance of programmed death-ligand 1 expression and microsatellite status in small bowel adenocarcinoma - Klose, Johannes; Lasitschka, Felix; Horsch, Cornelia; Strowitzki, Moritz; Bruckner, Thomas; Volz, Claudia; Schmidt, Thomas; Schneider, Martin (Scandinavian journal of gastroenterology, 2020)
Background: Small bowel adenocarcinoma (SBA) is a dreadful disease. Patient prognosis is limited due to late presentation and ineffective chemotherapy. PD-1/PD-L1 checkpoint immunotherapy is regarded as a promising approach in several cancer entities. The association of PD-1/PD-L1 expression and its impact on patient prognosis with SBA is unclear. Material and methods: Seventy-five consecutive patients who underwent surgery for SBA were retrospectively analyzed and stained for PD-L1 expression in the tumour or the stroma. Analysis of mismatch repair genes was performed to determine microsatellite status. Kaplan-Meier estimate was used to analyze patient survival. Univariate and multivariable Cox regression-analyses were used to assess the impact of PD-L1 expression and microsatellite status on patient survival.Results: PD-L1 was weakly upregulated within the tumour or the stroma and associated with prolonged survival (p = .0071 and p = .0472, respectively). Fifty-one tumours (68%) revealed microsatellite stability (MSS) and 24 tumours (32%) were microsatellite instable (MSI) without correlating with patient survival (p = .611). Neither PD-L1 expression in the tumour nor in the stroma was identified as an independent risk factor influencing survival (p = .572 and p = .3055).Conclusion: Although PD-L1 expression is associated with prolonged survival, it was not identified as an independent prognostic marker. Microsatellite status did not influence long-term survival.
Gesehen am 17.04.2020